PENGEMBANGAN PEMBELAJARAN MANAJEMEN DATABASE BERBASIS WEB CMS JOOMLA PADA MAHASISWA PENDIDIKAN ADMINISTRASI PERKANTORAN FAKULTAS EKONOMI UNIVERSITAS NEGERI JAKARTA - RONI Faslah (Jurnal Ilmiah Econosains, 2015)
Abstract This study aims to research, develop, test, and validate learning media database management for students in courses of Economic Education Department of Economics and Administration Faculty of Economics, University of Jakarta. Second, this development aims to produce instructional media in the form of web-based learning with joomla cms. Third, determine the thoroughness of learning outcomes and student response to the learning process with the media joomla website. This development method using silklus research and development (R & D Cycle) from Borg and Gall (1983) were modified. Based on the results of expert assessment, teachers and field trials on the product web-based learning media cms joomla, has obtained results that product development is considered feasible and has been able to facilitate the achievement of learning objectives. The results of field tests of the experimental class in this development means that the student assessment shows that the analysis of the media validator developed a valid entry in the category with a score of validity of 3.45. Criteria practicality of this medium can also be fulfilled for media media joomla website developed can be used with minimal revision. Student Learning Results showed that 31 students have a positive impact as indicated by the increased value of learning outcomes. The response of students to instructional media joomla website shows that as many as 96% of the students showed a positive response to learning this media joomla website. Keywords: development, R & D, database management, cms joomla